Synthesis of RpoS is dependent on a putative enhancer binding protein Rrp2 in Borrelia burgdorferi. - Zhiming Ouyang; Jianli Zhou; Michael V Norgard (PLoS ONE, 2014)
The RpoN-RpoS regulatory pathway plays a central role in governing adaptive changes by B. burgdorferi when the pathogen shuttles between its tick vector and mammalian hosts. In general, transcriptional activation of bacterial RpoN (σ54)-dependent genes requires an enhancer binding protein. B. burgdorferi encodes the putative enhancer binding protein Rrp2. Previous studies have revealed that the expression of σ54-dependent rpoS was abolished in an rrp2 point mutant. However, direct evidence linking the production of Rrp2 in B. burgdorferi and the expression of rpoS has been lacking, primarily due to the inability to inactivate rrp2 via deletion or insertion mutagenesis. Herein we introduced a regulatable (IPTG-inducible) rrp2 expression shuttle plasmid into B. burgdorferi, and found that the controlled up-regulation of Rrp2 resulted in the induction of σ54-dependent rpoS expression. Moreover, we created an rrp2 conditional lethal mutant in virulent B. burgdorferi. By exploiting this conditional mutant, we were able to experimentally manipulate the temporal level of Rrp2 expression in B. burgdorferi, and examine its direct impact on activation of the RpoN-RpoS regulatory pathway. Our data revealed that the synthesis of RpoS was coincident with the IPTG-induced Rrp2 levels in B. burgdorferi. In addition, the synthesis of OspC, a lipoprotein required by B. burgdorferi to establish mammalian infection, was rescued in the rrp2 point mutant when RpoS production was restored, suggesting that Rrp2 influences ospC expression indirectly via its control over RpoS. These data demonstrate that Rrp2 is required for the synthesis of RpoS, presumably via its action as an enhancer binding protein for the activation of RpoN and subsequent transcription of rpoS in B. burgdorferi.